Children's Reading Park as a Means of Learning Information in the Village of Situ Pete Sukadamai Tanah Sareal Bogor - Subagyo, Wawan Hari; Hamzah, Zeze Zakaria; Muhlis, Muhlis; Mujito, Mujito; Ikhsani, Adinda Nurul; Kusmiaji, Adelia (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Education plays a crucial role in developing high-quality and sustainable communities, with reading as a fundamental foundation in the educational process. Reading skills provide access to knowledge and foster deep understanding, critical thinking, and personal development. In Kampung Situpete Sukadamai Tanah Sareal Bogor, the primary challenges include low children's reading interest, limited access to books, and a lack of awareness about the importance of reading. To address these challenges, this community service project aims to establish a Children's Reading Garden (TBA) in Kampung Situpete. This initiative is designed to enhance children's reading interest, improve the reading culture, and support education by providing quality books and supporting programs such as reading clubs, book performances, and creativity classes. Community involvement, including parents and local leaders, is encouraged through workshops and volunteer participation. The method employed is Participatory Action Research (PAR), which focuses on empowering the community and involving them in the change process. The project, running from June to August 2024, includes ongoing monitoring and evaluation to ensure the effectiveness of the TBA. The initiative is expected to significantly contribute to advancing education and strengthening the reading culture within the Kampung Situpete community.